35
Пошаговое объяснение:
(x + 76):7 = 15
x+76 = 15*7
x+76 = 105
x = 105-76
x = 29
24:(х-3) = 8
x-3 = 24:8
x-3 = 3
x = 3+3
x = 6
Сумма корней = 29 + 6 = 35
ответ: корень 1 уравнения х+76=7*15=105 или х=105-76=29. Корень второго х-3=3 или х=6. Их сумма 29+6=35.
ответ 35.
35
Пошаговое объяснение:
(x + 76):7 = 15
x+76 = 15*7
x+76 = 105
x = 105-76
x = 29
24:(х-3) = 8
x-3 = 24:8
x-3 = 3
x = 3+3
x = 6
Сумма корней = 29 + 6 = 35
ответ: корень 1 уравнения х+76=7*15=105 или х=105-76=29. Корень второго х-3=3 или х=6. Их сумма 29+6=35.
ответ 35.
Пошаговое объяснение: